Shock engineering the additive manufactured graphene-metal nanocomposite with high density nanotwins and dislocations for ultra-stable mechanical properties. (15th May 2018) - Lin, Dong; Motlag, Maithilee; Saei, Mojib; Jin, Shengyu; Rahimi, Raheleh Mohammad; Bahr, David; Cheng, Gary J.
Abstract: Graphene reinforced metal composite has been a promising materials with superior mechanical properties. Currently the mechanical properties of the additively manufactured metals are limited by the undesired microstructures and residual stress developed during the laser heating process. Strengthening in graphene/metal composite is limited to the intrinsic strength of graphene and its ability to block dislocation from propagation, which make it very difficult to introduce dislocation hardening and twin boundary strengthening. Here, a hybrid manufacturing process combining layer by layer laser deposition of graphene/metal nanocomposites and laser shock peening has been investigated through modeling and experiments. Strengthening of graphene/metal composites is introduced by the strong interactions between shock wave and selective laser sintered graphene/metal composite. Instead of constraining the dislocation motion, graphene acts as a shock-loading transferor to allow shock wave to pass through and bounce back between them, resulting in high density dislocations and nanotwinning structures around graphene/metal interface. Molecular dynamics (MD) simulation shows that the shock interaction with the graphene/metal interface generates dislocations pile-up in front of graphene and large stress intensity around the interface. Wave-like nanowrinkles in graphene are generated after laser shock loading because of interference wave propagation. Mechanical testing results showed that the laser shock treated graphene/metal composites enable ultra-stability of strength and compressive residual stress, and excellent fatigue performance. MD simulation revealed that shock wave strengthened graphene/metal interface significantly reduces the crack propagation rate and provides strong resistance to fatigue of metal/graphene composites. Graphical abstract: Image 1